OPTIMIZATION OF THE OPERATION SUBSYSTEM OF EXTERNAL MEMORY IN THE COMPOSITION OF SSD AND HDD (Modern information system and technologies, 2018)
Considered the possibility of optimizing the functioning of the subsystem external memory, which consists of the system SSD and file storage in HDD, a personal computer running Microsoft WINDOWS 10. The goal of optimization is minimization of the latency of the specified subsystem under the condition of maximizing the duration of the life cycle of the SSD.